Comunicación y empoderamiento ciudadano en salud: un caso de investigación-acción en la Venezuela polarizada - Nahón-Serfaty, Isaac; Eid, Mahmoud (Revista Iberoamericana de Estudios de Desarrollo)
An action-research project was implemented in Venezuela from 2009-2013 to empower social activists and patients in their fight against breast cancer (BC). The project was implemented in a context of high political and social polarization of the so-called «Bolivarian revolution». Based on an ecological perspective of health activism and communication, that encompasses the interpersonal, group and social levels, a series of activities were celebrated to develop the advocacy capabilities of citizens, especially women, expand the collaborative networks among different stakeholders, and promote a consensual view between social and institutional actors about a national response to fight BC. A horizontal and participatory communication allowed that the voice of usually marginalized actors was heard in the process of shaping health care policy